Determinants and psychosocial effects of teenage pregnancy among public secondary schools in selected towns in Oye Local Government, Ekiti State, Nigeria (Multi-disciplinary Journal of Research and Development Perspectives, 2026)
Teenage pregnancy occurs when a teenage girl between the ages of 13-19 becomes pregnant as a result of unprotected sexual intercourse. This is a menace among secondary school teenagers in the study area. This study examined the determinants and perceived psychosocial effects of teenage pregnancy among public secondary schools in some selected towns in Oye Local Government, Ekiti State. To achieve the objectives of this study, data were collected through quantitative research method. The quantitative data focused mainly on the teenagersthrough the use of semi-structured questionnaire. A non-probability sampling technique was used to select these respondents. A total number of 200 respondents were involved in this research. The data obtained were analyzed using Statistical Package for Social Sciences (SPSS). The psycho-social effects of teenage pregnancy among teenagers are sense of guilt, loss of focus in education, depression, low self- esteem, limited social interaction. The major factor influencing teenage pregnancy was media influence, teenagers exposed to watching of sexual content on Television, lack of proper sex education among teenagers, alcohol and drugs abuse, poverty, peer pressure and broken homes. The study recommended an intensified sex education, control of social media and television content, better parental guidance, drugs and alcohol control.
Keywords: Determinants; psycho-social effect; secondary school students; teenage pregnancy